An Investigation of the Relationship Between Emergency Medicine Trainee Burnout and Clinical Performance in a High‐fidelity Simulation Environment. Issue 1 (January 2017) - Lu, Dave W.; Dresden, Scott M.; Mark Courtney, D.; Salzman, David H.
Abstract: Objective: Burnout is prevalent among emergency medicine (EM) physicians, with physicians experiencing burnout more likely to report committing medical errors or delivering suboptimal care. The relationship between physician burnout and identifiable differences in clinical care, however, remains unclear. We examined if EM trainee burnout was associated with differences in clinical performance using high‐fidelity simulation as a proxy for patient care. Methods: In this cross‐sectional study across six institutions, we measured trainee performance over four simulation scenarios based on recognized EM milestones. For each scenario a faculty rater assessed whether the trainee performed predefined critical actions specific to each case. A summation of performed actions across all cases resulted in a cumulative task (CT) score (range = 0–85). Raters also assigned an impression score on a 10‐point scale (0 = poor; 10 = outstanding) assessing the trainee's overall performance after each scenario, with the mean of the scores resulting in an overall impression (OI) score. After the simulation assessment, we measured trainees' burnout via the Maslach Burnout Inventory through a confidential, electronic survey. Trainee depression, quality of life (QOL) and daytime sleepiness were also evaluated. Survey results were compared to simulation scores using analysis of variance and covariance. Results: Fifty‐eight of 89 (65.2%) eligible participants completed the survey and simulation assessment. Thirty‐one of 58 (53.4%, 95% CI = 40.2% to 66.7%) trainees reported burnout. In trainees with burnout compared to those without, mean CT scores (73.4 vs. 75.2, 95% CI of difference = 0.06 to 3.51) and OI scores (6.4 vs 6.8, 95% CI of difference = 0.03 to 0.79) were negatively associated with burnout after controlling for training program. In contrast, QOL were positively associated with CT [F(1, 48) = 4.796, p = 0.033] and OI [F(1, 48) = 4.561, p = 0.038] scores. There were no significant associations between simulation performance and depression or daytime sleepiness. Conclusion: Emergency medicine trainees with burnout received lower cumulative performance scores over four high‐fidelity simulation scenarios than trainees without burnout.